IMPLEMENTATION OF TARGET COSTING IN TEGALSARI MSMEs, SURABAYA CITY - Pramandyah Fitah Kusuma; Desy Ismah Anggraini (SEAN Institute, 2023)
Target costing is a method that can be used to determine the target price and the maximum cost for a product to be able to achieve the expected profit. Target costing is the right method to use for businesses in the face of increasingly competitive competition. The purpose of this study was to find out whether target costing can be applied by MSMEs in Teglasari District, Surabaya City, especially food and can increase competitiveness. The results showed that several MSMEs in Tegalsari District, especially food in Surabaya, had implemented target costing and had an impact on increasing competitiveness along with increasing profits earned.